Prey and habitat availability in the Whiskey Jack Forest (Kenora Management Unit, Ontario) to support a cougar (Puma concolor) population - Hauck, Kathryn (2000)
Cougars (Puma concolor) are the largest of the cats found in Canada. Abundant now only in British Columbia and Alberta, cougars are possibly making a comeback in their former eastern range. One ‘sighting’ (scat and tracks), of a cougar was confirmed from the Whiskey Jack Forest during January and February 2000, Herb Lake location. I surveyed 37 kilometres of transects in the Whiskey Jack Forest to determine prey and habitat potential to support a viable cougar population. Eleven transects located in the northern section of Wildlife Management Unit (WMU) 7B, and 10 transects located in the southern section of WMU 6 were surveyed. Combining the Silver Lake and Jones Study Areas, results showed that ecosite 13 had the most abundant animal activity (1.94 animal tracks and trails/10m), followed by ecosites 11 (1.66 animal tracks and trails/10m), rock (1.46 animal tracks and trails/10m), ecosite 19 (1.42 animal tracks and trails/10m), and ecosite 14 (1.21 animal tracks and trails/10m). Snowshoe hare, Lepus americamus, was the most abundant prey species identified on all transects. Wolves, Canis lupus, a competitor of the cougar, were also abundant on many of the transects, indicating possible competition for habitat and prey resources. Deer (Odocoileus virginianus), the primary prey of cougar, were only found on one transect, which could indicate possible problems for permanent cougar residence in this area. Moose, Alces alces, however, were quite abundant on many of the transects and have some potential to support the predators. Whether or not the area can support cougars is unclear. Increasing the amount of time (consecutive winters) allocated to the study and the size of the study area surveyed would strengthen the study.